The Effect of Sleep Apnea on QT Interval, QT Dispersion, and Arrhythmias - Barta, Kitti (Clin Cardiol, 2010)
BACKGROUND: QT interval (QT) and QT dispersion (QTd) are electrocardiograph (ECG) parameters for the evaluation of myocardial repolarization. The inhomogeneity of ventricular repolarization is associated with ventricular arrhythmias. An increased QT, QTd, and increased incidence of nocturnal cardiac rhythm disturbances have been described in patients with obstructive sleep apnea (OSA), while other investigators did not find a relationship between ventricular arrhythmias and OSA. HYPOTHESIS: The aim of this study was to examine the occurrence of ventricular arrhythmias and to measure QT parameters in patients with untreated OSA using an ambulatory Holter‐ECG. METHODS: A total of 25 patients with untreated OSA were studied. After routine biochemical investigation and 2‐dimensional, M‐mode echocardiography, a 24‐hour Holter‐ECG was recorded to detect cardiac arrhythmias and QT parameters. QT parameters were measured by the QT Guard system. RESULTS: Only the QT interval increased significantly during the nighttime period (nocturnal QT interval: 423.1 ± 34.6 ms, daytime QT interval: 381.6 ± 33.8 ms, 24‐hour QT interval: 394.7 ± 31.1 ms). However, during the nighttime QT interval (422.8 ± 14.9 ms), QTd (31.2 ± 11.0 ms) and QT dispersion (30.5 ± 10.2 ms) did not show any change compared to 24‐hour (QTc interval: 423.7 ± 14.2 ms, QTd: 28.8 ± 9.4 ms, QTcd: 30.5 ± 9.43 ms) and daytime levels (QTc interval: 423.9 ± 14.3 ms, QTd: 27.3 ± 10.7 ms, QTcd: 29.9 ± 11.1 ms). None of the patients had ventricular arrhythmias. CONCLUSIONS: QTd and QTcd did not increase during the nighttime period. Our study did not show an increased risk of ventricular arrhythmias in this population during the monitoring period. Copyright © 2010 Wiley Periodicals, Inc.